Perancangan E – Learning Beladiri Praktis Bagi Mahasiswi UHAMKA Guna Menghindari Kejahatan Dan Pelecehan Seksual Berbasis Moodle - Hasan Dhiaulhaq Thalib; Isa Faqihuddin Hanif (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
Technology is currently experiencing rapid progress in the community, of course as a society that keeps up with the times, it must always be up to date for technology, especially in the learning process for students and schoolgirls, where in this difficult year in 2020 many students learn through the E process. Learning, therefore the author tries to design Moodle-based learning programs. Moodle as a supporting tool for making electronic learning, where the self-defense learning method is not only done face-to-face, therefore the authors try to develop it by learning virtual and mobile , this study aims to apply information technology for students to learn practical martial arts as a method of self-defense from all the dangers around us, the system designed by the author is an easy and practical system that can be accessed by many people, because Moodle is currently developing. rapidly with a variety of learning methods for those who use it as a form of virtual learning, in addition to being easily accessible and easy to learn as an admin, you can use the Moodle application, because its use is not too complicated to learn, and can save data. tabase learning via localhost / phpmyadmin / as material to store and create a Moodle learning database. This design uses the waterfall method so that it is easy to help others how to use the moodle.